Time-Related Vascular Inflammatory Response to COVID-19 Assessed by 18F-FDG PET/CT in Follow-Up Tumor Patients - Lin R; Yu J; Tian A; Wang X; Yuan X; Xu W; Xie W (Dove Medical Press, 2023)
Runlong Lin,1,2 Jing Yu,2 Aijuan Tian,2 Xiaomei Wang,2 Xin Yuan,2 Wengui Xu,1 Wenli Xie3 1Department of Molecular Imaging and Nuclear Medicine, Tianjin Medical University Cancer Institute and Hospital, National Clinical Research Center for Cancer, Tianjin Key Laboratory of Cancer Prevention and Therapy, Tianjin's Clinical Research Center for Cancer, Tianjin, People's Republic of China; 2Department of Nuclear Medicine, The Second Hospital of Dalian Medical University, Dalian, People's Republic of China; 3Department of Cardiovascular Medicine, The Second Hospital of Dalian Medical University, Dalian, People's Republic of ChinaCorrespondence: Wengui Xu, Department of Molecular Imaging and Nuclear Medicine, Tianjin Medical University Cancer Institute and Hospital, National Clinical Research Center for Cancer, Tianjin Key Laboratory of Cancer Prevention and Therapy, Tianjin's Clinical Research Center for Cancer, No. 1 Huanhu West Road, Tianjin, 300060, People's Republic of China, Tel +86-22-23340123, Email wenguixutj@126.com Wenli Xie, Department of Cardiovascular Medicine, The Second Hospital of Dalian Medical University, No. 467 Zhongshan Road, Dalian, Liaoning, 116023, People's Republic of China, Tel +86-411-84671291, Email dali1990@163.comPurpose: This study aimed to assess COVID-19's effects on vascular inflammatory response, by evaluating 18-Fluorodeoxyglucose (18F-FDG) uptake via positron emission tomography/computed tomography (PET/CT) in the artery of diffuse large B cell lymphoma (DLBCL) patients before and after infection with COVID-19.Patients and Methods: Thirty-five DLBCL patients administered the chemotherapy regimen R-CHOP and examined by oncological 18F-FDG PET/CT imaging twice from August 2022 to February 2023 for pre-treatment evaluation or assessment of treatment efficacy were enrolled. Seventeen patients were confirmed with COVID-19 within the study period. Arterial wall FDG uptake was semi-quantitatively analyzed as TBR (target-to-blood pool ratio) in 14 different vascular regions using oncological 18F-FDG PET/CT. Based on COVID-19 course and the two PET/CT scans, we further analyzed time-related FDG uptake for vascular walls in DLBCL patients with COVID-19.Results: Arterial TBRs were higher in the last PET/CT examination than previous ones in all patients with or without COVID-19. Besides the ascending aorta, ΔTBR (last PET/CT scanning's TBR minus previous PET/CT scanning's TBR) were not significantly different between the COVID-19 and Control groups. However, cases scanned ≤ 30 days from infection had remarkably higher ΔTBRs in comparison with those assessed > 30 days post-infection in the COVID-19 group (p< 0.05). A moderate inverse correlation was observed between ∆Global TBR (last PET/CT scanning's average TBR value minus previous PET/CT scanning's average TBR value) and time distance from COVID-19 onset to 18F-FDG PET/CT scan (Spearman's rho=− 0.591, P=0.012). Interestingly, there were no differences of changes of TBR between different purpose of PET/CT examination group.Conclusion: This work firstly suggested vascular inflammation is elevated in the early post-COVID-19 phase in DLBCL cases compared with prolonged post-COVID-19 phase or controls. Increasing attention should be paid to these patients and the protection of their vascular function and complications in early COVID-19.Keywords: 18F-FDG PET/CT, vascular inflammation, COVID-19, endothelial dysfunction, non-Hodgkin lymphoma